Informal but not Insignificant: Unregistered Workers in North Cyprus - Mustafa Besim; Glenn P. Jenkins (Queen's University, Department of Economics, 2006)
The size of the informal labour force and its contribution to the national income of North Cyprus has been an issue of considerable controversy and political significance. Because of the relatively free movement of labour between Turkey and North Cyprus, a significant body of unregistered workers have accumulated in North Cyprus. The findings are that from 1996 to 2000 the informal employment is between 35 to 40 per cent of the total labour force. Because not all the informal sectors production is excluded from the official national income statistics, the understatement of the official statistics is estimated to be between 12 to 17 percent of GNP. The fiscal losses are estimated to be about 9 percent of total tax revenues and a loss of social security revenues is approximately 38 per cent of the total annual contributions.
Keywords: H26; H24; 330; Cyprus; informal sector; informal labour force; fiscal losses; unrecorded income; underground economy